A modified Johnson-Cook constitutive model for structural steel after cooling from high temperature. (18th July 2022) - Zhu, Hongjie; Zhang, Chuntao; Chen, Shicai; Wu, Junjie
Highlights: A new constitutive model for high temperature cooled steel is proposed. Mechanical properties of natural cooled Q345B, Q460 and Q690D steels are studied. Both temperature and steel grade have significant effect on the mechanical properties. Yield strength and ultimate strength reduced when steel is cooled above 700 °C. Ductility increased when steel is naturally cooledfrom high temperatures. Abstract: High temperature has a significant impact on the mechanical properties of steel structural members, which can develop a potential collapse. Currently, various studies have been concentrating on the post-fire mechanical properties of different steels, while few of them considered the corresponding constitutive model. Therefore, in this paper, the classical Johnson-Cook constitutive equation is selected as a benchmark and is modified to fit the conditions in which the effects of heating and cooling on the mechanical properties of fire-affected steel are considered. To this end, three commonly used structural steels, namely Q345B, Q460 and Q690D, are selected in this paper. First, the specimens were heated to different target temperatures, and then naturally cooled down to the ambient temperature in the air. After cooling from the exposure temperatures, the subsequent tensile tests were performed on the fire-affected specimens to capture the failure modes and study the residual mechanical properties. To verify the proposed constitutive model, an Abaqus subroutine (UMAT) program was developed in this study. The experimental data of water-cooled specimens obtained in our previous studies were also selected to further test the feasibility of this new model. The results show that the exposure temperature and steel grade have significant effects on the residual mechanical properties of the structural steel specimens when the target temperature exceeds 700 °C. Meanwhile, the modified Johnson-Cook constitutive is able to predict the stress –strain behavior precisely, regardless of the cooling method. The results obtained in this study are helpful for both further research and engineering application when doing a numerical study of the fire-affected steel structures.